Open for Whom? An Equity Analysis of New York City's Open Streets Program - Figueroa, Erwin. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Sumeeta Srinivasan.; Committee: Mark Chase.; Keywords: Urban planning, and Transportation.